The democratic equality of the lot: from the niche of the legal system back to the polis - Ehs, Tamara (Momentum Quarterly, 2019)
The political lottery (sortition), a classic in the history of political ideas, is now again in use. Wherever representative democracy is confronted with a crisis of confidence, more and more citizens’ assemblies or councils drafted by lot appear on the scene. They are supposed to bring people into the political process who are not already active citizens by themselves, offering a non-populist measure of participation. Starting from a historical overview, the article explains how the lottery process outlasted in the legal system alone during the development of the modern state, but is now being rediscovered and promoted in the face of the democratic crisis in order to achieve more equality and egalitarianism, and even higher legitimacy for political decisions.